2019
DOI: 10.1590/0100-3984.2018.0024
|View full text |Cite
|
Sign up to set email alerts
|

Detection of additional primary malignancies: the role of CT and PET/CT combined with multiple percutaneous biopsy

Abstract: Objective: To evaluate the imaging findings of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) and computed tomography (CT) in patients with additional primary tumors, correlating the results with those of the method used in order to elucidate the diagnosis and of the pathology reports. Materials and Methods: We retrospectively analyzed the medical records, pathology reports and images of 11 patients who underwent CT, 18F-FDG PET/CT, or both. We included patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…The detection rate in this study (3.26%) in relatively in concordance to Ali et al [10], who had shown similar detection rate 13 out of 273 patients (4.76%) with the lower PPV of 56.5% and sensitivity of 89.2% and discordance to Servente et al [11] who showed less detection rate (1.2%, 49/4086) and Tibana and Lee [3,12] who had shown lesser detection rate (1.1).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The detection rate in this study (3.26%) in relatively in concordance to Ali et al [10], who had shown similar detection rate 13 out of 273 patients (4.76%) with the lower PPV of 56.5% and sensitivity of 89.2% and discordance to Servente et al [11] who showed less detection rate (1.2%, 49/4086) and Tibana and Lee [3,12] who had shown lesser detection rate (1.1).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the foremost common location of the second primary tumor was colon (n = 5) and lung (n = 5) in concordance to Servente et al [11] who histologically confirmed second primary in colon (n = 18), lung (n = 6), breast (n = 6), and in discordance to study of Tibana et al [3] who found most common sites of the additional malignancies were the lung (n = 4), kidney (n = 3), and prostate (n = 2).…”
Section: Multiple Primaries In Lymphomasupporting
confidence: 90%
See 1 more Smart Citation
“…Both the primary tumour and associated tumours in adjacent and/or distant organs can be detected [23]. However, despite the interesting perspective that is achieved by high-quality multiplanar reconstruction MDCT imaging and its utility in the correct assessment of tumour extension, CT sensitivity in discovering further tumours is relatively low (85-90%), especially in the case of lesions not distinguishable from benign abnormality (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Once the diagnosis is established, the standard treatment options are the administration of antibiotics, open perineal drainage, and transurethral resection of the prostatic abscess. Currently, however, minimally invasive procedures such as needle aspiration guided by imaging methods are well established in interventional radiology practice and are preferable to conventional methods, with low rates of complications and satisfactory therapeutic results (1)(2)(3)(4)(5)(6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%